Treatment-Resistant Hypertension in Individuals of High BMI - Akram, Mohammad Zeeshan; Mansoor, Khurram; Rasheed, Khurram; Maken, Ghulam Rasool; Faheem, Muhammad; Mujahid, Mamoon (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of treatment-resistant hypertension in individuals of high BMI and factors associated with resistant hypertension Study Design: Comparative cross-sectional studyPlace and Duration of Study: Pak Emirates Military hospital , Rawalpindi Pakistan,from Nov 2020 to Oct 2021.Methodology: Patients being managed for essential hypertension at the medical outpatient department were included in the study. Body mass index was calculated at the time of routine evaluation during the outpatient visit, and a detailed evaluation regarding the number of anti-hypertensive medications used was carried out on patients with a body mass index>25.Resistant hypertension was diagnosed if the blood pressure of the patient was not controlled on three or more antihypertensive medications.Results: A total of 600 patients with hypertension and a body mass index of more than 25 were included in the final analysis. Out of 600 patients, 489(81.5%) had essential hypertension, which was not treatment resistant, while 111(18.5%) had resistant hypertension. Statistical analysis showed that type 2 diabetes mellitus and cigarette smoking had a statistically significant relationship (p-value